FINANCIAL DEEPENING AND POVERTY REDUCTION: EVIDENCE FROM NIGERIA - Okafor, Emeka John (International Journal of Allied Research in Economics (IJARE), 2024)
Macroeconomic policies are fundamental for achieving key national objectives such as sustained economic growth, reduction of inequality, full employment, price stability, balance of payments equilibrium, and exchange rate stability. These goals are interrelated and collectively aim to enhance the overall wellbeing of the population. Effective monetary and fiscal policies are essential for pursuing these objectives, and their success largely depends on the level of financial development (or deepening) within a nation. Financial deepening plays a critical role in amplifying the potency of monetary policy and facilitating the attainment of macroeconomic goals. Additionally, safeguarding the life and property of citizens is a core component of these policies. This paper examines the relationship between financial deepening and the effectiveness of macroeconomic policies, highlighting how advancements in financial development can contribute to achieving the broader economic and social objectives of a nation